O circuito espacial produtivo dos fertilizantes no território brasileiro - Corrêa, Jeferson Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper has two main objective the study of the productive space circuit of fertilizers in Brazil. For this, we study the company's operations Vale Fertilizers SA More specifically, the production and consumption of fertilizers in Brazil. In the current globalization the Brazilian countryside know new ways of doing (SANTOS, 1994). This, with less roughness, adopts the Green Revolution package, and introduces inputs to the soil, such as seeders, combines, tractors, herbicides, fungicides and fertilizers (Santos & Silveira, 2001). The examination of the Brazilian case as the agricultural modernization reveals the great vulnerability of modern agricultural regions in the face of globalizing modernization (Santos, 2000: 92). The places that receive capital reproduction of imperatives gain a new medium, is the formation of informational scientific technical means, are the bright spots corresponding to other places (Santos, 1994). Thus, the productive circuits are no longer confined to the environment, but establish connections with distant places (Santos, 1986; Frederick & CASTILLO, 2004). What's more, the policy is now made in the market (Santos, 2000, p.67) and the adoption by the Brazilian government's neoliberal policies, the Brazilian state-owned companies related to fertilizer production circuit are privatized, thereby Brazil makes It is further more dependent on inputs used in the field, including fertilizers

Nosso trabalho tem por objetivo central o estudo do circuito espacial produtivo dos fertilizantes no território brasileiro. Para isso, estudamos a atuação da empresa Vale Fertilizantes S.A. mais especificamente, a produção e o consumo dos fertilizantes no território brasileiro. Na atual globalização o campo brasileiro conhece novas formas de fazer (SANTOS, 1994). Esse, com menos rugosidades, adota o pacote da Revolução Verde, e introduz insumos ao solo, tais como semeadeiras, colheitadeiras, tratores, herbicidas, fungicidas e fertilizantes (SANTOS & SILVEIRA, 2001). O exame do caso brasileiro quanto à modernização agrícola revela a grande vulnerabilidade das regiões agrícolas modernas em face da modernização globalizadora (SANTOS, 2000: 92). Os lugares que recebem os imperativos da reprodução do capital ganham um novo meio, é a formação do meio técnico científico informacional, são os pontos luminosos, lugares correspondentes a outros (SANTOS,1994). Com isso, os circuitos produtivos não mais são circunscritos ao entorno, e sim estabelecem conexões com lugares distantes (SANTOS, 1986; FREDERICO & CASTILLO, 2004). E mais ainda, a política agora é feita no mercado (Santos, 2000, p.67) e com a adoção pelo governo brasileiro da política neoliberal, as empresas estatais brasileiras ligadas ao circuito de produção dos fertilizantes são privatizadas, desse modo o Brasil torna-se ainda mais dependente dos insumos usados no campo, inclusive dos fertilizantes
Keywords: Geografia agrícola - Brasil; Adubos e fertilizantes - Indústria; Globalização; Neoliberalismo